The Dynamics of Commercialization of Scientific Knowledge in Biotechnology and Nanotechnology - Gómez Uranga, Mikel; Etxebarria Kerexeta, Goio; Campàs-Velasco, Jordi (European planning studies, 2007)
We carry out an in-depth study of the growth, diffusion and reinforcement of knowledge in this article. We look for drivers to diffuse knowledge as to collaboration (between different research teams and between university and industry), regulations (on intellectual property rights, governmental), and broad lines of scientific research according to the financing methods used. The studies referred to in this article are linked to the creation and search for better commercialization conditions for the sciences and technologies associated with biosciences and nanosciences. Different paths of knowledge may be identified, according to the case. Certain kinds of drivers may be used more often than others, determined by the type of knowledge being dealt with. For instance, networking and collaboration between different research teams is one of the main activities necessary to innovate and to commercialize the products resulting from knowledge and research in those clusters. In other situations, it may be more suitable to reinforce knowledge diffusion through certain regulations. A case in point is the significance of the Bayh-Dole Act in the US, used to improve relationships between university and industry. Therefore, the aim of this article is to evaluate the type of drivers and the intensity required in each case. In general, in more advanced clusters and territories, drivers are more biased to creating conditions to commercialize science, and to a lesser extent, to government intervention to foster development. The two case studies we have chosen, i.e. the Barcelona biomedical cluster and the biosciences cluster in the Basque Country, call for drivers that are the same in certain regards but vary greatly in intensity. The simultaneous presence of all of these drivers works in an interrelated manner to activate the complex process of commercialization of science.